Harnessing the Benefits and Potentials of Consortium among Special Libraries in Malaysia: Proposed areas, Policy, Framework and Strategies for successful Collaborations - Assoc Prof Norma, Abu Seman; Mohd Sharif, Mohd Saad (PETRONAS, 2010)
Organized by PETRONAS in collaboration with Pustaka Sumber Ilmu, 15th – 17th May 2005 at Nikko Hotel Kuala Lumpur, Malaysia.